Studies on mechanical properties of luffa acutangula/lignite fly ash reinforced composites - Jino, R; Sriraman, M; Arthika, B; G. Ashok, K (International Journal of Engineering and Technology, 2018)
The demand  of  using natural fibers in various  applications were  increasing day by day due to its eco friendly nature over the artificial fiber based polymer matrix composites.  This paper describes the fabrication and evaluation of mechanical and thermal properties of Luffa Acutangula fiber with and without Lignite Fly Ash. The lignite fly ash was added as a filler material in the ratio of 0, 0.5, 1, 1.5, percent of weight along with the matrix and fiber. The laminates were fabricated using hand layup technique and the samples were prepared based on ASTM standards for testings.The tensile test was performed using universal testing machine. The addition of filler lignite fly ash has shown the improvement in mechanical and thermal properties of laminated composites. The Tensile, flexural, and compression test was conducted for the fabricated samples and it was observed that the influence of lignite fly ash on natural fiber leads to the increase in tensile strength and compressive strength but the flexural strength was reduced for the fabricated laminates with the filler material lignite fly ash. The morphological analysis was carried out for finding the fractured surface and material failures using scanning electron microscope (SEM).